1993
DOI: 10.1002/art.1780360515
|View full text |Cite
|
Sign up to set email alerts
|

Familial versus sporadic ankylosing spondylitis. two different diseases?

Abstract: Objective. To define potential differences and the possible contribution of susceptibility or severity genes in familial versus sporadic ankylosing spondylitis (AS).Methods. Three hundred twenty patients with AS were studied: 160 who had first-degree relatives with AS (familial) and 160 age-and sex-matched controls who had no first-degree relative with the disease (sporadic). Disease expression in the two groups was evaluated using an index of physical, psychological, and social functioning (the Arthritis Impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 9 publications
2
16
1
Order By: Relevance
“…Lower inflammatory conditions in spite of the higher prevalence of HLA-B27 in the familial AS group were remarkable in this report. This is similar to the findings from a study that showed that familial disease was milder in metrological measures than sporadic disease (11). To the best of our knowledge, this study is the first to examine familial AS and its clinical manifestations in Asia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Lower inflammatory conditions in spite of the higher prevalence of HLA-B27 in the familial AS group were remarkable in this report. This is similar to the findings from a study that showed that familial disease was milder in metrological measures than sporadic disease (11). To the best of our knowledge, this study is the first to examine familial AS and its clinical manifestations in Asia.…”
Section: Discussionsupporting
confidence: 90%
“…Subjective outcomes such as pain, disability and objective radiographic changes were influenced by familiality (10). A UK study reported that familial AS was a milder disease than the sporadic disease in terms of spinal mobility, physical, emotional and social well-being (11). According to a Spainish study, being female and having a young age at symptom onset, longer disease duration, uveitis, HLA-B27, higher pain visual analogue scale (VAS), higher Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and a good response to non-steroidal anti-inflammatory drugs (NSAIDs) were reported to be associated with familiality (12).…”
Section: Introductionmentioning
confidence: 99%
“…In one study [26], familial versus sporadic Dutch AS patients exhibited no difference in age at disease onset, age at diagnosis, or prevalence of peripheral arthritis and acute anterior uveitis. In another study, familial AS disease was significantly milder than sporadic disease, as assessed by spinal mobility score, Arthritis Impact Measurement Scales (AIMS) overall impact score, AIMS physical activity score, AIMS social function score and AIMS pain score [27]. Thus, findings from multiplex families might not be directly applicable to individuals affected with sporadic AS.…”
Section: Discussionmentioning
confidence: 99%
“…For CD, an earlier age of onset and a higher frequency of exclusively colonic disease was shown in familial cases [41][42][43][44][45]. The familial form of AS is associated with a milder disease phenotype [46], and high heritability of disease severity was shown [47,48]. To what extent these observations hold true in mixed SpA/IBD families is not known.…”
Section: Familial Clustering Of Spondyloarthro-pathy and Inflammatorymentioning
confidence: 99%